Post-exercise Warm or Cold Water Immersion to Augment the Cardiometabolic Benefits of Exercise Training: A Proof of Concept Trial - Russell, Brooke M.; Chang, Courtney R.; Hill, Terry; Cotter, James D.; Francois, Monique E. (Frontiers in Physiology, 2021)
We investigated whether substituting the final half within 60-min bouts of exercise with passive warm or cold water immersion would provide similar or greater benefits for cardiometabolic health. Thirty healthy participants were randomised to two of three short-term training interventions in a partial crossover (12 sessions over 14-16 d, four week washout): i) EXS: 60 min cycling 70% maximum heart rate (HRmax), ii) WWI: 30 min cycling then 30 min warm water (38-40C) immersion, and/or iii) CWI: 30 min cycling then 30 min cold water (10-12C) immersion. Before and after, participants completed a 20 min cycle work trial, V ̇O2max test, and an Oral Glucose Tolerance Test during which indirect calorimetry was used to measure substrate oxidation and metabolic flexibility (slope of fasting to postprandial glucose oxidation). Data from twenty two participants (25±5 y, BMI 23±3 kg/m2, Female=11) were analysed using a fixed-effects linear mixed model. V ̇O2max increased more in EXS (interaction p=0.004) than CWI (95% CI: 1.1, 5.3 mL/kg/min, Cohen’s d= 1.35), but not WWI (CI: -0.4, 3.9 mL/kg/min, d= 0.72). Work trial distance and power increased 383 ± 223 m and 20 ± 6W, respectively, without differences between interventions (interaction both p>0.68). WWI lowered postprandial glucose ~9% (CI -1.9, -0.5 mmol/L; d= 0.63), with no difference between interventions (interaction p= 0.469). Substituting the second half of exercise with WWI provides similar cardiometabolic health benefits to time matched exercise, however substituting with CWI does not.